Prototype of Fish Drying Device for the Production of Salted Fish Based on IoT - Rezeki, Sri; Novriyenni; Milli Alfhi Syari (Yayasan Kita Menulis, 2024)
The prototype of the fish drying tool for the production of salted fish is designed to enhance efficiency and control in the salted fish drying process by utilizing IoT technology to monitor and regulate the drying environment conditions. The DHT22 sensor connected to port D5 is used to measure temperature and humidity inside the drying room. The data collected by this sensor is sent to a microcontroller connected to a relay to control the heater and DC fan, as well as a buzzer as a warning system if the room temperature exceeds 60° C. The Blynk application is used for a user interface that allows for the remote monitoring and adjustment of drying parameters via a smartphone. The test results show that this system is capable of maintaining the conditions for drying salted fish within optimal temperature and humidity ranges, thereby improving the quality and efficiency of the drying process. The integration of IoT technology in this device facilitates monitoring and control, as well as enhancing the overall effectiveness of the drying process.